Oxysophocarpine Ameliorates Carrageenan-induced Inflammatory Pain via Inhibiting Expressions of Prostaglandin E2 and Cytokines in Mice - Yang, Yang; Li, Yu-Xiang; Wang, Hong-Ling; Jin, Shao-Ju; Zhou, Ru; Qiao, Hai-Qi; Du, Juan; Wu, Jing; Zhao, Cheng-Jun; Niu, Yang; Sun, Tao; Yu, Jian-Qiang (Planta Medica, 2015)
Oxysophocarpine is an alkaloid extracted from Sophora alopecuroides. We investigated the analgesic effect of oxysophocarpine on carrageenan-induced inflammatory pain in mice, in order to explore its possible mechanisms. Mouse ear swelling tests and carrageenan-induced paw edema tests were used to investigate the effects of oxysophocarpine on inflammatory pain in mice. Morphological changes on inflamed paw sections were measured by hematoxylin-eosin staining. The mRNA and protein expression of extracellular signal-regulated kinase, phosphorylation of extracellular signal-regulated kinase 1/2, cyclooxygenase-2, tumor necrosis factor α, interleukin-1 beta, interleukin-6 and prostaglandin E2 were investigated by real-time quantitative polymerase chain reaction, immunohistochemistry, western-blot and enzyme-linked immunosorbent assay. In our results, oxysophocarpine shows a significant anti-inflammatory effect in the mouse ear swelling test. Oxysophocarpine also significantly reduced the paw edema volume and improved mechanical allodynia threshold value on carrageenan-induced inflammatory pain, as well as relieved paw tissues inflammatory damage and reduced the numbers of neutrophils in mice. Oxysophocarpine significantly suppressed over-expression of cyclooxygenase-2, tumor necrosis factor α, interleukin-1 beta, interleukin-6 and prostaglandin E2, and inhibited the over-phosphorylation of extracellular signal-regulated kinase 1/2. Based on these findings we propose that oxysophocarpine attenuates inflammatory pain by suppressing the levels of phosphorylation of extracellular signal-regulated kinase 1/2, cyclooxygenase-2, prostaglandin E2, tumor necrosis factor α, interleukin-1 beta and interleukin-6.
Keywords: Sophora alopecuroides; Leguminosae; oxysophocarpine; inflammation pain; pro-inflammatory cytokines; prostaglandin E2